2006
DOI: 10.1074/jbc.m510369200
|View full text |Cite
|
Sign up to set email alerts
|

Examining Ty3 Polypurine Tract Structure and Function by Nucleoside Analog Interference

Abstract: We have combined nucleoside analog interference with chemical footprinting, thermal denaturation, NMR spectroscopy, and biochemical studies to understand recognition of the polypurine tract (PPT) primer of the Saccharomyces cerevisiae long terminal repeatcontaining retrotransposon Ty3 by its cognate reverse transcriptase. Locked nucleic acid analogs, which constrain sugar ring geometry, were introduced pairwise throughout the PPT (؊)-DNA template, whereas abasic tetrahydrofuran linkages, which lack the nucleob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…To explore this notion, we have inserted a variety of nucleoside analogs into PPT-containing RNA/DNA hybrids to alter their structure in a manner that minimally alters sequence context. Examples include pyrimidine isosteres, or shape mimics, which locally remove hydrogen bonding (12,17), abasic tetrahydrofuran linkages, which remove the nucleobase while preserving the sugar-phosphate backbone (18,19), pyrrolo-dC, a fluorescent cytosine analog providing information on local base pairing (20) and locked nucleic acid monomers, which locally stabilize the phosphate backbone. This strategy demonstrated (i) that the junction between the rG:dC and upstream rA:dT tract is particularly sensitive to altering hydrogen bonding (17) (ii) weakened base pairing at position −2 (20) and (iii) that DNA nucleobases on either side of the PPT-U3 junction are not required for accurate cleavage (18).…”
Section: Introductionmentioning
confidence: 99%
“…To explore this notion, we have inserted a variety of nucleoside analogs into PPT-containing RNA/DNA hybrids to alter their structure in a manner that minimally alters sequence context. Examples include pyrimidine isosteres, or shape mimics, which locally remove hydrogen bonding (12,17), abasic tetrahydrofuran linkages, which remove the nucleobase while preserving the sugar-phosphate backbone (18,19), pyrrolo-dC, a fluorescent cytosine analog providing information on local base pairing (20) and locked nucleic acid monomers, which locally stabilize the phosphate backbone. This strategy demonstrated (i) that the junction between the rG:dC and upstream rA:dT tract is particularly sensitive to altering hydrogen bonding (17) (ii) weakened base pairing at position −2 (20) and (iii) that DNA nucleobases on either side of the PPT-U3 junction are not required for accurate cleavage (18).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this model, site-directed mutagenesis has demonstrated that substituting Phe-61 alters fidelity (34), processivity, and strand displacement synthesis (35). The focus of the present study was to determine whether (a) altering the nucleobase, sugar, or phosphate backbone of the 5Ј template overhang ahead of the polymerase catalytic center influences orientation of the template base and (b) how this is affected by substitution of amino acids implicated in such interactions.The strategy we pursued is based on our recent analysis of (ϩ) strand DNA synthesis from the polypurine tract primer of retroviruses (25,26,28) and long terminal repeat-containing retrotransposons (36,37). In these studies nucleoside analogs altering duplex geometry were exploited to define regions of the polypurine tract-containing RNA/DNA hybrid interacting with the cognate RT.…”
mentioning
confidence: 99%
“…The strategy we pursued is based on our recent analysis of (ϩ) strand DNA synthesis from the polypurine tract primer of retroviruses (25,26,28) and long terminal repeat-containing retrotransposons (36,37). In these studies nucleoside analogs altering duplex geometry were exploited to define regions of the polypurine tract-containing RNA/DNA hybrid interacting with the cognate RT.…”
mentioning
confidence: 99%
“…If the sites were functionally independent, each should exhibit a binding affinity similar to that of PPT wt . While coupling between NB binding sites on the Ty3 PPT was unexpected, propagation of structural signals has been observed along the rA·rG·rA symmetric steps of the PPT with both dF base analogue (9) and LNA-substituted PPTs (36). …”
Section: Discussionmentioning
confidence: 97%